Adapting to an evolving market: A framework for business model innovation in the carbon dioxide removal market - Karlsson, Lovisa; Allgöwer, Louise (My University, 2026)
The Carbon Dioxide Removal (CDR) market is rapidly evolving and is increasingly recognized as an important complement to emission reductions in addressing climate change. However, the market remains uncertain and fragmented, creating challenges for both buyers and providers of carbon dioxide removal credits. This thesis explores industrial buyers’ preferences, needs and barriers related to the purchase of carbon dioxide removal credits. It also explores how CDR providers can adapt their business models and operations accordingly. The study aims to contribute insights that support the continued development and adoption of CDR solutions. A qualitative research approach was applied, centered around a main case, a marine CDR provider, and additional interviews with buyers, intermediaries and certifiers, complemented with secondary data. Two research questions guided the study: How do industrial buyers select CDR providers and what hinders buyer adoption of CDR? and How can CDR providers innovate their business model to adapt to industrial buyer preferences and needs? The findings show that buyers evaluate providers based on several choice factors such as trustworthiness and transparency, proximity, storytelling, price-fit and growth potential, as well as characteristics of CDR method. The findings also revealed several barriers limiting the adoption of CDR such as price uncertainty, regulatory uncertainty and evolving standards, high market complexity and shifting perceptions of CDR. A framework integrating business model innovation and dynamic capabilities with the synthesized findings was developed. The framework illustrates how providers can use sensing, seizing and transforming capabilities to identify market signals, adapt their business models and continuously reconfigure their operations in response to changing customer needs and market conditions. Based on the findings several practical recommendations for providers are identified.
Keywords: Carbon dioxide removal; complex market, evolving market; carbon credits; dynamic capabilities; business model innovation